الجنسية الأصلية دراسة مقارنة الجزائر-تونس - هيثم قرفي; محمد الأمين صياد (My University, 2020)
Summary Every child, regardless of his descent or where he was born, has the right to enjoy nationality. The original nationality of a person is the legal association between himself and the State and proves that he belongs to it, whether based on the right of blood as an original criterion for establishing the original nationality or the right to extraordinary nationality. It is also possible for a person to enjoy more than one native nationality simultaneously and thus be multinational, They may also be non-nationals. And both phenomena cause problems for the individual on one side and for the state on the other, so the doctrine just sought to find solutions for both phenomena. Legislation has included legal means of establishing or denying an individual's citizenship within the laws of her nationality. In the light of these legislation, Algerian and Tunisian legislation provides that each of them has legally defined the methods of proof, without failing to refer to the proceedings relating to nationality, as highlighted by the competent judicial authorities for the consideration and adjudication of matters relating thereto. This determines the argument of the judgments handed down in these matters, all because of the importance of nationality in the individual's life as the most important link of common law, which defines one of the pillars of the State, which is the people. ,,,,,,,,,,,,,,,,,,,,,,,,, ﻣﻠﺧص ﻛل ﻣوﻟود ﺑﻐض اﻟﻧظر ﻋن اﻟﻧﺳل اﻟذي ﯾﻧﺣدر ﻣﻧﻪ أو اﻟﻣﻛﺎن اﻟذي وﻟد ﻓﯾﻪ ﻟﻪ اﻟﺣق ﺑﺎﻟﺗﻣﺗﻊ اﻟﺟﻧﺳﯾﺔ، ﻓﺎﻟﺟﻧﺳﯾﺔ اﻷﺻﻠﯾﺔ اﻟﺗﻲ ﯾﺗﻣﺗﻊ ﺑﻬﺎ اﻟﺷﺧص ﻫﻲ الراﺑطﺔ اﻟﻘﺎﻧوﻧﯾﺔ اﻟﺗﻲ ﺗرﺑط ﺑﯾﻧﻪ وﺑﯾن اﻟدوﻟﺔ وﺗﺛﺑت إﻧﺗﻣﺎﺋﻪ ﻟﻬﺎ ﺳواء ﻛﺎن ذﻟك اﺳﺗﻧﺎدا إﻟﻰ ﺣق اﻟدم ﻛﻣﻌﯾﺎر أﺻﻠﻲ ﻟﺛﺑوت اﻟﺟﻧﺳﯾﺔ اﻷﺻﻠﯾﺔ أو ﺣق اﻹﻗﻠﯾم ﻛﻣﻌﯾﺎر إﺳﺗﺛﻧﺎﺋﻲ .ﻛﻣﺎ أﻧﻪ ﻣن اﻟﻣﻣﻛن ﻟﻠﺷﺧص أن ﯾﺗﻣﺗﻊ ﺑﺄﻛﺛر ﻣن ﺟﻧﺳﯾﺔ أﺻﻠﯾﺔ ﻓﻲ آن واﺣد وﺑﺎﻟﺗﺎﻟﻲ ﯾﻛون ﻣﺗﻌدد اﻟﺟﻧﺳﯾﺎت، ﻛﻣﺎ ﻗد ﯾﻛون ﻏﯾر ﺣﺎﻣﻼ ﻷي ﺟﻧﺳﯾﺔ ﻓﯾﻛون ﻋدﯾم اﻟﺟﻧﺳﯾﺔ، وﻛﻼ اﻟظﺎﻫرﺗﯾن ﺗﺳﺑﺑﺎن ﻣﺷﺎﻛل ﻟﻠﻔرد ﻣن ﻧﺎﺣﯾﺔ وﻟﻠدوﻟﺔ ﻣن ﻧﺎﺣﯾﺔ أﺧرى، ﻟذﻟك ﺳﻌﻰ اﻟﻔﻘﻪ ﺣدﯾﺛﺎ إﻟﻰ إﯾﺟﺎد ﺣﻠول ﻟﻛﻼ اﻟظﺎﻫرﺗﯾن. وﻟﻘد ﺗﺿﻣﻧت اﻟﺗﺷرﯾﻌﺎت اﻟﺳﺑل اﻟﻘﺎﻧوﻧﯾﺔ ﻹﺛﺑﺎت أو ﻧﻔﻲ ﺗﻣﺗﻊ اﻟﻔرد ﺑﺎﻟﺟﻧﺳﯾﺔ وذﻟك ﺿﻣن ﻗواﻧﯾن ﺟﻧﺳﯾﺗﻬﺎ، وﻣن ﺑﯾن ﻫذﻩ اﻟﺗﺷرﯾﻌﺎت ﻧﺟد اﻟﺗﺷرﯾﻌﯾن اﻟﺟزاﺋري واﻟﺗوﻧﺳﻲ، ﺣﯾث أن ﻛل ﻣﻧﻬﻣﺎ ﺣدد ﺑﺻﻔﺔ ﻗﺎﻧوﻧﯾﺔ طرق اﻹﺛﺑﺎت دون أن ﯾﻐﻔل اﻹﺷﺎرة إﻟﻰ اﻟدﻋﺎوى اﻟﻣﺗﻌﻠﻘﺔ ﺑﺎﻟﺟﻧﺳﯾﺔ ﻣﺑرزا ﻓﻲ ذﻟك اﻟﺟﻬﺎت اﻟﻘﺿﺎﺋﯾﺔ اﻟﻣﺧﺗﺻﺔ ﺑﺎﻟﻧظر واﻟﻔﺻل ﻓﻲ اﻟﻣﺳﺎﺋل اﻟﻣﺗﻌﻠﻘﺔ ﺑﻬﺎ، ﻣﺣدد ﺑذﻟك ﺣﺟﯾﺔ اﻷﺣﻛﺎم اﻟﺻﺎدرة ﻓﻲ ﻫذﻩ اﻟﻣﺳﺎﺋل، وﻛل ذﻟك ﻟﻣﺎ ﻣن اﻟﺟﻧﺳﯾﺔ ﻣن أﻫﻣﯾﺔ ﺑﺎﻟﻐﺔ ﻓﻲ ﺣﯾﺎة اﻟﻔرد ﺑﺈﻋﺗﺑﺎرﻫﺎ أﻫم رواﺑط اﻟﻘﺎﻧون اﻟﻌﺎم واﻟﺗﻲ ﺗﺣدد رﻛن ﻣن أرﻛﺎن اﻟدوﻟﺔ واﻟﻣﺗﻣﺛل ﻓﻲ اﻟﺷﻌب. ,,,,,,,,,,,,,,,,,,,,,,, Résumé Chaque enfant, quelle que soit sa descendance ou son lieu de naissance, a le droit de jouir de la nationalité. La nationalité d’origine d’une personne est l’association juridique entre elle-même et l’État et prouve qu’elle lui appartient, que ce soit sur la base du droit au sang comme critère original d’établissement de la nationalité d’origine ou du droit à la nationalité extraordinaire. Il est également possible pour une personne de jouir de plus d’une nationalité autochtone simultanément et donc être multinationale, ils peuvent également être non-nationaux. Et les deux phénomènes causent des problèmes à l’individu d’un côté et à l’État de l’autre, de sorte que la doctrine a simplement cherché à trouver des solutions pour les deux phénomènes. La législation a inclus des moyens légaux d’établir ou de refuser la citoyenneté d’une personne dans les lois de sa nationalité. A la lumière de ces législations, la législation algérienne et tunisienne prévoit que chacune d’elles a défini juridiquement les modalités de preuve, sans omettre de se référer à la procédure relative à la nationalité, comme l’ont souligné les autorités judiciaires compétentes pour l’examen et l’arbitrage des questions y afférentes. Cela détermine l’argument des arrêts rendus dans ces matières, tout cela en raison de l’importance de la nationalité dans la vie de l’individu comme le lien le plus important de la common law, qui définit l’un des piliers de l’État, qui est le peuple.